Solve for u 5+3u=-1

Math
5+3u=-1
Move all terms not containing u to the right side of the equation.
Tap for more steps…
Subtract 5 from both sides of the equation.
3u=-1-5
Subtract 5 from -1.
3u=-6
3u=-6
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3u=-6 by 3.
3u3=-63
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3u3=-63
Divide u by 1.
u=-63
u=-63
Divide -6 by 3.
u=-2
u=-2
Solve for u 5+3u=-1

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top